Power imbalance in hospital dual management system and its impact on turnover - Zhang, Manli; Guo, Qianqian; Pathak, Janak L.; Ou, Vian; Li, Le; Trigo, Virginia (Frontiers in Public Health, 2024)
Introduction With the deepening of the healthcare reform in China, the competition in the sector is becoming fiercer leading to several unintended consequences such as talent turnover, which highly affect hospital development. Taking the case of a specialized university-affiliated stomatology hospital in Guangzhou, this thesis aims to analyze the main factors that contribute to talent turnover in this type of hospitals. The loss of talents in the field of stomatology is not unique to China and represents a significant problem in both developed and developing countries. Methods The data for the study were collected from post facto live interviews conducted with 21 resigners to understand their feelings and motivations after the passage of time. The data were coded and concepts refined using MAXQDA software to form 18 sub-categories and 6 aggregate dimensions leading to the construction of two theoretical models.The balance of power embedded in the dual leadership system characteristic of Chinese organizations and corresponding leadership style and behavior, deeply affect the turnover of talents. The more unbalanced the power, the greater the impact on turnover. Conclusions Based on the situation studied, a power imbalance allowed for individual behaviors that determined the development of the hospital and directly affected institutional fairness, culture, working atmosphere and ultimately led to turnover.